Impact of gender on survival of out-of-hospital cardiac arrest presenting with refractory ventricular arrhythmias and role of coronary artery disease. (19th May 2022) - Caputo, ML; Baldi, E; Krull, JD; Cresta, R; Benvenuti, C; Primi, R; Currao, A; Bendotti, S; Compagnoni, S; Gentile, FR; Savastano, S; Klersy, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Clinical presentation and outcome of out-of-hospital cardiac arrest (OHCA) presenting with shockable rhythm may vary between males and females. Very limited data exist on gender-related differences in OHCAs with refractory ventricular arrhythmias (VA) and, in particular, on distribution and prevalence of coronary artery disease (CAD). Purpose: The aim of this study was to characterize gender-related outcome, prevalence and severity of CAD in OHCA victims presenting with shockable rhythm and refractory VA. Methods: All OHCAs presenting with shockable rhythm occurred between 2015 and 2019 in the province of Pavia (Italy) and in the Canton Ticino (Switzerland) were included. Results: Out of 3592 OHCAs, 685 presented with shockable rhythm and, of them, 212 had a refractory VA. Overall, male gender was independently associated with a lower probability of survival both at hospital admission and at 30-days (OR 0.63, 95% CI 0.58-0.67, p <0.001 and OR 0.82 95% CI 0.74-0.91, p <0.001, respectively) and presented with a more severe CAD. Male gender was 5-times more frequently associated with OHCA presenting with refractory VA. Despite of a more favourable OHCA presentation (i.e. more often OHCA witnessed, public place occurrence and CPR initiated by bystander) male patients with refractory VA had a lower likelihood of survival (OR 0.25, 95% CI 0.21-0.30). A higher prevalence (81%) of CAD was observed in OHCAs presenting with refractory VA but not a higher number of diseased vessels. Conclusions: Male gender is more frequently associated with refractory VA, lower probability of survival and higher prevalence and severity of CAD. CAD severity, however, does not significantly affect refractory VA presentation.